An Investigation into Cash Flow Forecasts Practices - Kum, Chi Leng (2010)
Cash flow forecasts are the most important step in the capital budgeting process in terms of planning effectively to finance for cash deficit and invest cash surplus for capital expenditure decisions. Despite its importance, little progress has been made in its estimation process, due to the difficulty of producing accurate cash flow numbers for the analysis of capital budgeting decisions. This management project details the investigation of the cash flow forecasts practices and highlights some of the challenges in such forecasts.